G‐Quadruplex‐Binding Small Molecule Induces Synthetic Lethality in Breast Cancer Cells by Inhibiting c‐MYC and BCL2 Expression. (12th December 2019) - Paul, Rakesh; Das, Tania; Debnath, Manish; Chauhan, Ajay; Dash, Jyotirmayee
Abstract: Herein, a prolinamide‐derived peptidomimetic that preferentially binds to c‐MYC and BCL2 G‐quadruplexes present in the promoter regions of apoptosis‐related genes ( c‐MYC and BCL2 ) over other DNA quadruplexes are described. Biological assays, such as real‐time quantitative reverse transcription, western blot, dual luciferase, and small interfering RNA knockdown assays, indicate that the ligand triggers a synthetic lethal interaction by simultaneously inhibiting the expression of c‐MYC and BCL2 genes through their promoter G‐quadruplexes. The ligand shows antiproliferative activity in MCF‐7 cells that overexpress both MYC and BCL2 genes, in comparison to cells that overexpress either of the two. Moreover, the ligand induces S‐phase cell‐cycle arrest, DNA damage, and apoptosis in MCF‐7 cells. Abstract : Deadly interactions : Ligand 1 inhibits c‐MYC and BCL2 expression by stabilizing their promoter quadruplexes; this leads to S‐phase arrest, DNA damage, and apoptosis by synthetic lethal interaction in MCF‐7 cells.